The switched capacitor inverter as a MPPT in a photovoltaic application - Marouchos, Christos; Xenofontos, Despo; Darwish, Mohamed K.; Moghadam, Mansour Salehi; Armefti, Christina (My University, 2014)
The new topology for a dc to ac converter based on the switched capacitor circuit was introduced recently. The promising features of low harmonic content, high efficiency, MPPT facility and voltage step up characteristics makes it a good candidate for grid connected-renewable energy sources. The harmonic content is further minimised in this paper by introducing multiple current modulators, each connected to a PV panel. It is also shown that the circuit also tracks the Maximum Power Point of the output power of the photovoltaic panel with varying irradiation from the sunand ambient temperature. The work is carried out by extensive simulations on PSIM.
Keywords: Grid-connected Inverters; Inverters; Multilevel inverters